ANALISIS PENGUKURAN KINERJA DENGAN PENDEKATAN BALANCED SCORECARD PADA RUMAH SAKIT SULTAN DG. RAJA BULUKUMBA - Andi rustam; Ismail Rosulong; Andi Nur Aziza (INVOICE : JURNAL ILMU AKUNTANSI, 2019)
This study aims to determine the performance of Sultan Hospital Dg. King of Bulukumba when measured using the Balanced Scorecard approach. The analytical method used is descriptive analysis with a quantitative approach using hospital performance indicators in performing performance measurements. The results of the study show generally that 1) Sultan Hospital Dg. Raja Bulukumba allows to apply the Balanced Scorecard to measure organizational performance, because with the Balanced Scorecard all aspects can be measured. The application of the Balanced Scorecard is possible because the Sultan Hospital Dg. The King of Bulukumba has formulated his vision, mission and strategy and the results of the research show that the performance of Sultan Hospital Dg. The King of Bulukumba is said to be quite good when using the Balanced Scorecard. And 2) performance measurement of Sultan Hospital Dg. The King of Bulukumba using the Balanced Scorecard for a period of 2 years shows good results